A review of some models for the analysis of contingency tables : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Statistics at Massey University - Anderson, Julie Anne (Massey University, 1988)
Some models proposed for the analysis of contingency tables are reviewed and illustrated with examples. These include standard loglinear models; models which are suitable for ordinal categorical variables such as ordinal loglinear, log multiplicative and logit models, and models based on an underlying distribution for the response; and models for incomplete and square tables. Estimation methods and inference are also discussed.
Keywords: Contingency tables -- Analysis; Mathematical models